2009
DOI: 10.1111/j.1556-4029.2009.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Age Estimation from the Anterior Cortex of the Femur in Korean Adults*

Abstract: The purpose of this study was to develop age-predicting equations from the anterior cortex of the femur of Korean adults. Seventy-two femoral samples (44 male and 28 female) were obtained from Korean cadavers and used to develop the equations. The thin sections (<100-microm thick) were prepared by manual grinding; the sections were not decalcified and were stained with Villanueva bone stain reagent. Analysis of covariance showed no significant differences in age-adjusted histomorphological variables between se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
(29 reference statements)
2
24
0
6
Order By: Relevance
“…Variation has been reported at various organizational levels, from the bone to the population. A tendency for secondary osteons to be smaller in older people has been reported (Takahashi et al, 1965; Han et al, 2009), but the absence of this relationship has also been noted (Black et al, 1974; Burr et al, 1990; Pfeiffer et al, 2006; Lee et al, 2014). Recent study of cortical bone of the femoral neck region has reported a significant negative association between On.Ar and age (Tong et al, 2015), while another study reports a negative association between On.Ar and body weight, but not age (Britz et al, 2009).…”
mentioning
confidence: 95%
“…Variation has been reported at various organizational levels, from the bone to the population. A tendency for secondary osteons to be smaller in older people has been reported (Takahashi et al, 1965; Han et al, 2009), but the absence of this relationship has also been noted (Black et al, 1974; Burr et al, 1990; Pfeiffer et al, 2006; Lee et al, 2014). Recent study of cortical bone of the femoral neck region has reported a significant negative association between On.Ar and age (Tong et al, 2015), while another study reports a negative association between On.Ar and body weight, but not age (Britz et al, 2009).…”
mentioning
confidence: 95%
“…En el campo antropológico y forense, el análisis histomorfométrico ha sido y es común-mente aplicado en la estimación de la edad a la muerte (Kerley, 1965;Singh y Gunberg, 1970;Stout, 1988;Ericksen, 1991;Yoshino et al, 1994;Watanabe et al, 1998;Vasallo, 2000;Cho et al, 2002;Maat et al, 2006;Nor et al, 2006;Han et al, 2009;Gomes et al, 2014), en estudios tafonómicos y diagenéticos (Bell, 2012), diferenciación taxonómica (Hillier y Bell, 2007;Martiniaková et al, 2006;Mulhern y Ubelaker, 2012;Crescimanno y Stout, 2012), análisis de actividad ocupacional y biomecánica (Robling y Stout, 2008;Skedros, 2012) entre otros.…”
Section: Estimación Histomorfométrica De La Edadunclassified
“…Stout and Paine, 1992;Stout et al, 1996;Crowder and Rosella, 2007;Kim et al, 2007;Pavón et al, 2010;Cho and Stout, 2011), long bones (e.g. Kerley, 1965;Singh and Gunberg, 1970;Kerley and Ubelaker, 1978;Pfeiffer, 1980;Stout and Gehlert, 1982;Frost, 1987;Stout and Stanley, 1991;Wallin et al, 1994;Ericksen, 1991 andEricksen and Stix, 1991;Lynnerup et al, 2006;Maat et al, 2006b;Chan et al, 2007;Robling and Stout, 2008;De Donno et al, 2009;Han et al, 2009;Villa and Lynnerup, 2010), and ilium (e.g. Boel et al, 2007).…”
Section: Estimation Of Age At Death In Skeletonized Human Remainsmentioning
confidence: 99%
“…Bell et al, 1996), the assessment of age-at-death estimation (e.g. Maat et al, 2006b;Crowder and Rosella, 2007;Kim et al, 2007;Han et al, 2009), and trauma analysis (e.g. Bartelink et al, 2001;Alunni-Perret et al, 2005).…”
Section: Forensic Anthropologymentioning
confidence: 99%